PENGARUH DISIPLIN KERJA, SEMANGAT KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN USAHA PERTUKANGAN (FURNICURE) RAHMAT BARAKA HOMBES KEC. BARAKA KAB. ENREKANG - Akmad, Akmad; Basri, Hasmawati (Perpustakaan dan Penerbitan Unismuh Makassar, 2015)
This research is to know the existence of significant influence between work discipline, morale and compensation to employee performance of Carpentry (Furniture) Rahmat Baraka Hombes Kecamatan Baraka Enrekang Regency partially and simultaneously. Analytical tool used in this research is multiple linear regression analysis, ujit, F test and coefficient of determination. Result of regression Y = 3,905 + 0,036 X1 + 0,019 X2 + 0,818 X3 + e. Based on the results of data processing above, then the compensation variable is the most dominant variable influence on employee performance.Result of t test of work discipline (X1) on employee performance (Y) obtained t value (0,757)> from t table (0,05) then Ho accepted, hence variable of work discipline no significant effect to employee performance. The result of F value arithmetic (17.233)> from the value of F table (2,867) then Ho is rejected so that there is a significant influence of work discipline, morale, compensation for employee performance together The calculation of SPSS program obtained by Adjusted R Square value = 0,590 means work discipline variable, morale, compensation gives 59% influence to employee performance, while the rest 41% influenced by other factors outside the variable studied, for example like work environment factor, communication and others.